Pre-sowing seed treatment of soybean seeds as approach to increase crop yield - Didorenko, S.V.; Kabylbekova, G.K.; Kassenov, R.Zh.; Dalibaeva, A.M.; Andrambayeva, N.S.; Derbush, S.N. («Академик Е.А. Бөкетов атындағы Қарағанды университеті» КЕАҚ баспасы, 2023)
Soybean holds a leading position in the world ranking o f the agricultural crops. The cultivated areas for this crop have been expanding in all countries of the global leaders in its production. In Kazakhstan, in recent years the cultivated areas have decreased from 139.5 thousand hectares in 2019 to 113.3 thousand hectares in 2021. This is due to the difficulty to grow the early-season varieties in the northern region of the Republic. The average crop yield o f soybean by region ranges from 3.0 c/ha in the north to 24.8 c/ha in southeastern Kazakhstan. The crop yield o f the developed and approved for production varieties can be increased by the additional agronomic techniques, including the pre-sowing seed treatment with the biologically active substances. This paper demonstrates the results o f the effect o f soybean seed treatment for different groups of maturity with the nitrogen-fixing inoculant HiStick and micronutrients o f Co and Mo. Profitability o f the conducted treatments was calculated. The pre-sowing treatment with salts o f molybdenum and cobalt is profitable to use for early-season variety Ivushka and full-season variety Lastochka. For the early ripening variety Birlik KV, the highest profitability was observed for the combined seed treatment with nitrogen-fixing inoculant HiStick and salts o f Mo and Co. In Zhansaya soybean variety, the application o f the additional treatments decreases the profitability o f production.
Өнімділікті арттыруға тәсіл ретінде соя тұқымдарын алдын ала өңдеу
Предварительная обработка семян сои в качестве подхода к повышению урожайности
Keywords: soybean; variety; nitrogen fixation; micronutrients; crop yield; profitability